Purpose-driven oral examination: insights from doctoral viva examiners - Wee Chun Tan (Springer, 2023)
Abstract Despite the importance of the PhD viva in assessing the quality of doctoral research, how examiners approach the PhD viva remains underexplored in the Global South. This study fills this gap by investigating the conceptions of doctoral examiners in Malaysia, shedding light on how they approach the PhD viva and what they believe its key purposes are. Through qualitative thematic analysis of interviews with twelve examiners, this study reveals that examiners place a significant emphasis on the quality of the research thesis, empower candidates to demonstrate mastery of the research subject, initiate dialogue for research engagement, and foster socialisation within the disciplinary community. The study contributes to the conceptualisation of the purposes of the PhD viva, encompassing gatekeeping, empowerment, dialogue, and enculturation, which can provide valuable guidance for examiner practices. The implications of these findings are discussed, highlighting the facilitative role of examiners in the examination process.